Co-precipitation method for the preparation of nanocrystalline ferroelectric SrBi2Nb2O9 ceramics - Gaikwad, S. P.; Dhage, S. R.; Potdar, H. S.; Samuel, V.; Ravi, V. (Journal of Electroceramics, 2005)
A simple co-precipitation technique had been successfully applied for the preparation of pure ultrafine single phase SrBi2Nb2O9. Ammonium hydroxide and ammonium oxalate were used to precipitate Sr2+, Bi3+ and Nb5+ cations simultaneously. No pyrochlore phase was found while heating powder at 850 C and pure SrBi2Nb2O9 (SBN) phase was formed as revealed by the X-ray diffraction (XRD) studies. Particle size and morphology was studied by transmission electron microscopy (TEM). The room temperature dielectric constant at 1 kHz is 100. The ferroelectric hysteresis loop parameters of these samples were also studied.
Keywords: Ceramics; Chemical synthesis; electronic materials; ferroelectricity; Oxides

Synthesis of rutile from ATO and stearic acid - Patil, M. M.; Deshpande, V. V.; Deshpande, S. B.; Samuel, V.; Ravi, V. (Materials Letters, 2005)
Nanocrystalline titanium dioxide in the rutile phase has been obtained from the solid state reaction between ammonium titanyl oxalate (ATO) and stearic acid at 400 degrees C in air. The fine powders of ATO and stearic acid are mixed well using acetone in an agate mortar and pestle for 2 h. This mixture (weight ratio of ATO to stearic acid > 5) on heating at 400 degrees C produces rutile powders. For the ratios of ATO to stearic acid < 5, a mixture of anatase and rutile phases is obtained. Pure ATO yields anatase phase on decomposition at 400 degrees C. These powders were characterized by X-ray diffraction (XRD), BET surface area measurements and transmission electron microscopy (TEM) studies. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Ceramics; Chemical synthesis; Electron microscopy; Oxides; X-ray techniques

Coprecipitation technique to prepare Sr0.5Ba0.5Nb2O6 - Murugan, A. Vadivel; Gaikwad, A. B.; Samuel, V.; Ravi, V. (Bulletin of Materials Science, 2006)
An aqueous mixture of ammonium oxalate and ammonium hydroxide was used to coprecipitate barium and strontium ions as oxalates and niobium ions as hydroxide under basic conditions. This precursor on calcining at 750 degrees C yielded Sr0.5Ba0.5Nb2O6 phase. This is a much lower temperature than that prepared by traditional solid state method (1000 degrees C) as reported for the formation of Sr0.5Ba0.5Nb2O6 (SBN). Transmission electron microscopic (TEM) investigations revealed that the average particle size was 80 nm for the calcined powders. The room temperature dielectric constant at I kHz was found to be 1100. The ferroelectric hysteresis loop parameters of these samples were also studied.
Keywords: Ceramics; Electron microscopy; ferroelectricity; Oxides; X-ray diffraction

Hydrothermal synthesis of MCM-41 using differently manufactured amorphous dioxosilicon sources - Gaydhankar, T. R.; Samuel, V.; Joshi, P. N. (Materials Letters, 2006)
The influence of differently manufactured amorphous dioxosilicon sources such as fumed silica (FS), spray dried precipitated silica (PSI) and flash dried precipitated silica (PS,) on the course of structural development and properties of hydrothermally prepared siliceous MCM-41 phases have been investigated. Powder XRD, N-2 adsorption/desorption and scanning electron microscopy techniques were used for sample characterization. On the basis of results obtained from time dependent study on the progressive development of MCM-41 mesophases, the reactivity trend of dioxosilicon sources observed was as: FS > PS1 > PS2. MCM-41 synthesized using least expensive PS2 having less surface area has exhibited thicker pore walls but poor orderness, while MCM-41 prepared from expensive FS having high surface area has thinner pore walls and was well ordered. The extent of contraction caused by calcination, magnitude of the wall thickness and structural stability were found to be dependent on manufacturing process of dioxosilicon sources. The noticeable morphological differences were also observed by variations in the type of dioxosilicon sources used in the hydrothermal synthesis MCM-41 materials. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Characterization; dioxosilicon sources; Hydrothermal synthesis; MCM-41; porosity; Structural stability

Phase evolution of NiTiO3 prepared by coprecipitation method - Murugan, A. Vadivel; Samuel, V.; Navale, S. C.; Ravi, V. (Materials Letters, 2006)
A simple coprecipitation technique was used for the preparation of NiTiO3 powders. Ammonium carbonate solution was added to a solution mixture containing stoichiometric amounts of Ni(NO3)(2) and TiOCl2 to precipitate nickel as carbonate and titanium as hydroxide under basic conditions. The precipitate was calcined at different temperatures ranging from 100 to 800 degrees C and phase evolution of NiTiO3 was investigated by X-ray diffraction (XRD) studies. It is observed that nickel titanate was formed at 750 degrees C. For comparison, NiTiO3 was also prepared by standard ceramic process. Particle size and morphology was studied by transmission electron microscopy (TEM). (c) 2005 Elsevier B.V. All fights reserved.
Keywords: Ceramics; Chemical synthesis; Electron microscopy; NiTiO3; Oxides; X-ray diffraction

Coprecipitation technique to prepare CoTa2O6 and CoNb2O6 - Mulla, Imtiaz S.; Natarajan, N.; Gaikwad, A. B.; Samuel, V.; Guptha, U. N.; Ravi, V. (Materials Letter, 2007)
An aqueous solution of sodium hydroxide was used to coprecipitate cobalt and tantalum (or niobium) ions from their precursors as hydroxides under basic conditions. This precipitate yielded CoTa2O6 (CT) or CoNb2O6 (CN) ceramics on calcining at 700 degrees C, i.e. at a temperature much lower than 900 degrees C, reported for the formation of these powders prepared by the traditional solid state method. The X-ray diffraction (XRD) studies were employed to investigate phase contents and lattice parameters. The morphology of the synthesized powders was investigated by transmission electron microscopy (TEM). (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Chemical synthesis; electronic materials; Oxides; X-ray methods

Coprecipitation technique to prepare NiNb2O6 - Samuel, V.; Gaikwad, A. B.; Jadhav, A. D.; Natarajan, N.; Ravi, V. (Materials Letter, 2007)
A mixture of ammonium carbonate and ammonium hydroxide was used to coprecipitate nickel and niobium ions as nickel carbonate and niobium hydroxide under basic conditions. This precursor yielded NiNb2O6 (NN) ceramics on calcining at 700 degrees C (at a temperature lower than 800 degrees C which is necessary for the formation of NiNb2O6 when prepared by the traditional solid state method). The average particle size and morphology of these powders were investigated by transmission electron microscope (TEM). (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Chemical synthesis; Electron microscopy; electronic materials; Oxides; X-ray methods

Low temperature route to prepare LaFeO3 and LaCoO3 - Jadhav, A. D.; Gaikwad, A. B.; Samuel, V.; Ravi, V. (Materials Letters, 2007)
A combination of digestion and further low temperature calcination to crystallize the product was employed to prepare LaFeO3 (LF) and LaCoO3 (LC) powders. Freshly co-precipitated lanthanum and ferric (or cobalt) hydroxide gels by sodium hydroxide were allowed to react at 100 degrees C under refluxing and stirring conditions for 4-6 h. These oven dried powders were heated at 450 degrees C to from crystalline LF (or LC) powders. The phase contents and lattice parameters were investigated by X-ray diffraction (XRD). Transmission electron microscope (TEM) investigations were carried out to examine the morphology and average particle size of these powders. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Chemical synthesis; LaFeO3; Precipitation; transmission electron microscopy; X-ray diffraction

Novel technique to prepare LiNbO3 at low temperature - Samuel, V.; Gaikwad, A. B.; Jadhav, A. D.; Mirji, S. A.; Ravi, V. (Materials Letter, 2007)
Fresh niobium hydroxide was first precipitated from NbF5 solution using an aqueous ammonium hydroxide under basic conditions. Then a simple procedure of mixing lithium and niobium hydroxides together and heating at a low temperature (400 degrees C) produced pure ultrafine single phase LiNbO3 (LN). In the literature, this is the lowest temperature so far reported on the formation of LN. The phase content and lattice parameters are determined by X-ray diffraction (XRD). The average particle size and morphology were studied by transmission electron microscopy (TEM). (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Chemical synthesis; Electron microscopy; electronic materials; LiNbO3; X-ray diffraction

Preparation of nanocrystalline ferroelectric CaBi4Ti4O15 by citrate gel method - Murugan, A. Vadivel; Gaikwad, A. B.; Samuel, V.; Ravi, V. (Ceramics International, 2007)
A gel was formed when an aqueous solution of CaCl2, BiNO3, TiOCl2 and citric acid in stoichiometric ratio is heated on a water bath. This gel on decomposition at 700 degrees C produced nano crystallites of the ternary oxide, CaBi4Ti4O15 (CBT). The phase contents and lattice parameters were studied by the powder X-ray diffraction (XRD). Particle size and morphology was studied by transmission electron spectroscopy (TEM). The room temperature dielectric constant at 1 kHz is 390. The ferroelectric hysteresis loop parameters of these samples were also studied by a home-built Sawyer-tower circuit. (c) 2006 Elsevier Ltd and Techna Group S.H. All rights reserved.
Keywords: Ceramics; Chemical synthesis; Electron microscopy; Oxides; X-ray methods

Synthesis of La0.7Sr0.3MnO3 at 800 degrees C using citrate gel method - Ravi, V.; Kulkarni, S. D.; Samuel, V.; Kale, Sangeeta N.; Mona, J.; Rajgopal, R.; Daundkar, A.; Lahoti, P. S.; Joshi, Rakesh S. (Ceramics International, 2007)
Manganite systems have been of considerable interest in the recent past due to their potential to operate in wide property range and also to serve as effective magnetic sensing and storing devices when synthesized using stringent conditions. We report a novel citrate gel method, in which La0.7Sr0.3MnO3 system has been synthesized at temperature 800 degrees C (LSMO800) with the synthesis duration is 6 h. The results have been compared with the sample synthesized at 1050 degrees C (LSMO1050). The synthesized bulk polycrystalline sample shows single-phase nature with the increase in particle size from similar to 50 nm to 300 nm with the increase in the sintering temperature. The magnetization data for LSMO800 shows well-defined hysteresis with saturation magnetization at around 1800 Oe and Curie temperature at 360 K, which is slightly lower than that of LSMO1050, which is 375 K. The results can be well attributed to the grain boundary effects. (C) 2006 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: Ceramics; Citrate gel method; CMR; Oxides

Titania nanoparticles synthesis in mesoporous molecular sieve MCM-41 - Lihitkar, N. B.; Abyaneh, Majid Kazemian; Samuel, V.; Pasricha, R.; Gosavi, S. W.; Kulkarni, S. K. (Journal of Colloid and Interface Science, 2007)
Nanocrystalline titanium oxide (TiO2) is one of the most useful oxide material, because of its widespread applications in photocatalysis, solar energy conversion, sensors and optoelectronics. The control of particle size and monodispersity of TiO2 nanoparticles is a challenging task. The use of MCM-41, an inorganic template of uniform pore size (2-10 nm), can overcome this difficulty and produce stable nanoparticles of uniform size and shape. Here, we demonstrate the synthesis of titania nanoparticles inside the pores of silica based MCM-41 forming a TiO2/Si-MCM composite. Composites are formed in the alcoholic medium by incipient wetness impregnation method. Titania particles of average 3 nm size are obtained. Effect of silica and titania precursors on the quality of nanoparticles has been investigated. The characterization of titania-MCM-41 composites has been carried out using a variety of techniques like UV-vis absorption spectroscopy, X-ray diffraction, FT-IR spectroscopy, X-ray photoelectron spectroscopy, transmission electron microscopy and photoluminescence spectroscopy. It has been found that the titania particles are co-ordinated with Si-MCM by Si-O-Ti covalent bond. (C) 2007 Elsevier Inc. All rights reserved.
Keywords: incipient wetness impregnation; Mesoporous material; template; titania

Co-precipitation method for preparation of Bi3TiNbO9 powders - Gupta, U. N.; Samuel, V.; Muthurajan, H.; Kumar, H. H.; Patil, S. D.; Ravi, V. (Ceramics International, 2008)
A simple co-precipitation technique has been successfully used for the preparation of pure, ultrafine, single phase Bi3TiNbO9 (BTN). An aqueous ammonium hydroxide solution was used to simultaneously precipitate Bi3+, Ti4+ and Nb5+, cations as hydroxides under basic conditions (pH similar to 9). No pyrochlore phase was found while heating powder at 500 degrees C and pure BTN phase was found to be formed by X-ray diffraction (XRD). For comparison, BTN samples were also synthesized by the traditional solid state method. The sequence of phase formation in both cases were investigated by XRD studies. (c) 2007 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: Ceramics; Chemical synthesis; electronic material; Oxides; XRD

Co-precipitation technique to prepare BiNbO4 powders - Radha, R.; Gupta, U. N.; Samuel, V.; Muthurajan, H.; Kumar, H. H.; Ravi, V. (Ceramics International, 2008)
A simple co-precipitation technique was successfully used for the preparation of pure ultrafine single phase BiNbO4. A standard ammonium hydroxide solution was used to precipitate Bi3+ and Ta5+ cations as hydroxides simultaneously under basic conditions. For comparison, BN powders were also prepared by the traditional solid-state method. It is observed that the co-precipitation technique produces BiNbO4 on heating at 600 degrees C, whereas complete phase formation occurs only at 800 degrees C in the solid-state method. The phase contents and lattice parameters were Studied by powder X-ray diffraction (XRD). (C) 2007 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: BiNbO4; Ceramics; Chemical synthesis; Electron microscopy; Oxides; X-ray diffraction

Novel hydroxide precursors to prepare NaNbO3 and KNbO3 - Muthurajan, H.; Kumar, H. H.; Samuel, V.; Gupta, U. N.; Ravi, V. (Ceramics International, 2008)
Firstly, fresh niobium, hydroxide was precipitated from NbF5 solution using an aqueous ammonium hydroxide under basic conditions. Then a simple procedure of mixing potassium (or sodium) and niobium hydroxides together and heating at a low temperature (<400 degrees C) produced KNbO3 (KN) or NaNbO3 (NN) powders. This is the lowest temperature so far reported for the formation of these phases. The phase content and lattice parameters are determined by X-ray diffraction (XRD). The average particle size and morphology were studied by scanning electron microscopy (SEM). (c) 2007 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: chemical preparation; niobates; Perovskites; powders; X-ray methods

Synthesis of bismuth titanate (Bi4Ti3O12)powders via calcination of microwave-hydrothermally (MH) derived precursor - Khollam, Y. B.; Deshpande, S. B.; Samuel, V.; Potdar, H. S. (Indian Journal of Engineering and Materials Sciences, 2008)
Micrometer sized platelet-like particles of bismuth titanate (Bi4Ti3O12) ire prepared successfully by the calcination of a mixed-precursor in air. The mixed precursor is precipitated Under microwave-hydrothermal (MH) treatment via dissolution-recrystallization kinetics. The mixed precursor is precipitated in-situ by giving MH treatment (at 200 degrees C, 200 psi, and 30 min hold time) to the hydrolysed slurry containing Bi and Ti cations. The slurry was prepared by adding 20% aqueous KOH precipitant solution to a well-mixed stoichiometric nitrate solution containing Bi and Ti cations. XRD results revealed that the as-dried precursor consisted of a homogenous mixture of non-crystalline particles of Bi2O3 and TiO2. The calcination of the as-dried precursor at 700 degrees C/2 h in air resulted ill the formation of micron sized platelet like single-phase Bi4Ti3O12 powders having orthorhombic structure.
Keywords: Bi4Ti3O12; MH processing; SEM; XRD

Gas-phase oxidant-free oxidation of cyclohexanol over V2O5-MoO3-M2O (M = Na, K, Cs) catalysts - Vyawahare, Y. K.; Chumbhale, Vilas R.; Pardhy, S. A.; Samuel, V.; Aswar, A. S. (Indian Journal of Chemical Technology, 2010)
Oxidant-free oxidation (dehydrogenation) of cyclohexanol is carried out in a down-flow integral laboratory scale reactor using different alkali doped catalysts. The effect of reaction temperature, contact time (W/F) and doping of alkali metals is studied to check its effect on nature of prominent products of the reaction (cyclohexanone and cyclohexene). At lower temperature the cyclohexanone prevails whereas at higher temperature cyclohexene is observed in prominence. Acid-modified catalysts (with boron and phosphorous) facilitated cyclohexene selectivity whereas alkali modified catalysts facilitated cyclohexanone selectivity. Calcination of sodium modified catalyst at different temperatures under static condition affect characteristic phase intensity and cyclohexanone selectivity. XRD investigation showed formation of different inorganic phases as the characteristic of dopant. Cesium modified catalyst showed better dehydrogenation activity.
Keywords: Cyclohexanol; dehydration; Dehydrogenation; Electronegativity; V2O5-MoO3

Synthesis of Sn-containing anatase (TiO2) by sol-gel method and their performance in catalytic water splitting under visible light as a function of tin content - Tangale, N. P.; Niphadkar, P. S.; Samuel, V.; Deshpande, Suvarna S.; Joshi, P. N.; Awate, S. V. (Materials Letters, 2016)
Sol-gel route was employed to prepare a series of Sn-containing anatase with different molar (Ti/Sn) ratios ranging from 49 to 1. Samples were characterized by powder XRD, UV-vis, XPS, SEM, EDAX, low temperature N-2 sorption technique and Raman Spectroscopy. Except anatase phase, no other crystalline phase was observed when Ti/Sn molar ratio was varied from 49 to 9 and for Sn free sample. However, further decrease in the ratio lead to the appearance of additional SnO2 phase whose peak intensities were increased with the increase in the tin content. Irrespective of tin content, all samples showed red-shift in UV-vis spectra. Moreover, samples showed Raman shift to higher vibration side from 143 cm(-1) to 147 cm(-1) indicating the doping of Sn2+ into TiO2. By virtue of low band gap, anatase crystallite size and an absence of XRD visible SnO2, ST (19) has shown maximum photocatalytic activity upon 1 wt% Pt loading. It has exhibited the highest rate (0.1264 mmole/g/h) for visible light induced hydrogen evolution by water splitting. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Semiconductors; Sn2+ doped titania; SnO2/TiO2; Sol-gel preparation; visible light; water splitting